A critical-point model to estimate damage caused by wheat leaf diseases in a multiple pathosystem Modelo de ponto crítico para estimar danos de doenças foliares do trigo em patossistema múltiplo - Bohatchuk D.A.* (2008)
Wheat leaf diseases cause damage by reducing photosynthetic activity in leaves. The objective was to obtain damage model equations for a wheat multiple pathosystem, by examining the relation between grain yield and the incidence of leaf diseases at different plant growth stages. The experiments were carried in Lages and Sẽo José do Cerrito, SC, during the 2005/06 and 2006/07 crop seasons with cultivars Ônix and BRS Louro. The gradient of disease incidence was obtained by the number of fungicide applications (one, two, and three) and three different fungicide rates: azoxystrobin+cyproconazol (40+16, 60+24 and 80+32 g of a.i. ha-1), trifloxystrobin+tebuconazol (25+50, 50+100 and 75+150 g of a.i. ha-1) and pyraclostrobin+epoxyconazol (33.25+12.5, 66.5+25 e 99.75+37.5 g of a.i. ha-1). Each experiment consisted of ten treatments distributed according to the random block scheme with four repetitions. The leaf disease incidence was evaluated at the growth stages EC 31, 34, 40, 52 and 60 according to Zadok's scale. There was significant correlation between two places and harvests for BRS Louro cultivar in the 40 and 50 plant growth stages. However, this was only significant for the Ônix cultivar in São José do Cerrito in both harvests. The variation between the damage model equations indicates the necessity to continue this research in different places and years, using cultivars with similar leaf disease reactions to those tested in this work. Copyright by the Brazilian Phytopathological Society.